How healthcare systems shape a purchaser's strategies and actions when managing chronic care. Issue 6 (June 2020) - Noort, Bart A.C.; Ahaus, Kees; van der Vaart, Taco; Chambers, Naomi; Sheaff, Rod
Highlights: Purchaser engagement strengthens purchasing but can involve high transaction costs. A purchaser's strategic lens should focus on chain-wide improvement but also on accessibility. A directive-influencing style enables chain-wide improvement but may create over-interference. Purchaser competition, purchaser governance and patient choice shape purchaser behaviour. Abstract: Healthcare purchasing organisations in both insurance-based and tax-based healthcare systems struggle to improve chronic care. A key challenge for purchasers is to deal with the chain of multiple providers involved in caring for patients with complex needs. To date, most research has focused on differences between healthcare systems in terms of regulation, tools and the freedom that healthcare purchasers have. However, this does not explain how such different healthcare system characteristics lead to different purchasing strategies and actions. A better understanding of this link between system characteristics and purchaser behaviour would assist policymakers seeking to improve healthcare purchasing. This multiple case study conducted in England, Sweden and the Netherlands examines the link between the different healthcare systems' characteristics and the purchasers' strategies and actions when managing chronic care chains. Purchasers' strategies and actions varied in terms of the purchaser's engagement, strategic lens and influencing style. Our findings suggest that differences in purchaser competition, purchaser governance and patient choice in healthcare systems are key factors in explaining a purchaser's strategies and actions when pursuing improvements in chronic care. This study contributes to knowledge on what shapes the purchaser's role, and shows how policymakers in both insurance- and tax-based regimes can improve healthcare purchasing.